Penggunaan Circuit Breaker SF6 Pada Gardu Traksi Di Jalur Kereta Rel Listrik Manggarai Jatinegara JIWP.pdf - Rozi, Mohamad Fatkur; Santoso, Dian Budhi; Ibrahim, Ibrahim (Peneliti.net, 2023)
The electric rail system uses a traction substation as a control center to regulate and manipulate the electric power used in train operations. One of the key components in a traction substation is the circuit breaker, which is responsible for breaking off the flow of electricity in the event of a disturbance or failure in the system. Circuit breaker SF6 (Sulfur Hexafluoride) is a type of circuit breaker that is often used in traction substation applications on electric railroads. SF6 has excellent insulation properties and high extinguishing ability, so it can cut off electricity quickly and efficiently in the event of a disturbance. In addition, SF6 gas has a high density, so the size of the SF6 circuit breaker is relatively smaller compared to other types of circuit breakers, making it suitable for use in confined spaces at traction substations. In the Manggarai-Jatinegara electric railroad line, the use of the SF6 circuit breaker at the traction substation provides several advantages. First, the SF6 circuit breaker can handle the high amperage used by electric trains, with sufficient breaking capacity. Second, the good insulation properties of SF6 help prevent voltage spikes that can damage sensitive electronic equipment in traction substations. Third, the compact size of the SF6 circuit breaker allows efficient use in confined spaces at the traction substation. However, the use of SF6 circuit breakers also has several challenges. One of them is the environmental impact of SF6 gas used as an arc extinguishing medium. SF6 is included in the greenhouse gases that have a high global warming potential. Therefore, it is important to ensure the use and processing of SF6 gas safely and responsibly so that environmental impacts can be minimized. In conclusion, the use of the SF6 circuit breaker at the traction substation on the Manggarai-Jatinegara electric railroad line provides advantages in terms of efficient breaking capability and compact size. However, it is necessary to remember to manage the environmental impact of using SF6 gas in a responsible manner.